THE EFFECT OF GOVERNMENT QUALITY ON FOREIGN DIRECT INVESTMENT IN ASEAN PLUS THREE - Maranik, Zita Fira; Iranto, Dicky; Mukhtar, Saparuddin (International Journal of Economy, Education and Entrepreneurship (IJE3), 2024)
This study aims to determine the effect of government quality on Foreign Direct Investment (FDI) in ASEAN Plus Three. Recent empirical studies have shown that FDI is expected to be strongly associated with good governance conditions in the host country. The research method used in this study is a quantitative approach. To accomplish this study, we used a panel data set of 13 countries in ASEAN Plus Three regions from 1996 to 2022. This analysis was conducted using a random effects model (REM). Our findings can be summarized: Government Effectiveness and the Rule of Law positively impact FDI in the ASEAN Plus Three Countries. Moreover, Political Stability, Voice, and Accountability have a negative impact on FDI. However, Regulatory Quality and Control of Corruption could be more significant in attracting FDI inflows